METABOLIC SURGERY VERSUS CLINICAL TREATMENT: COMPARISON OF COSTS AND EFFICACY IN THE MANAGEMENT OF MORBID OBESITY - Pedro do Valle Varela, João; Clara Berzoini Albuquerque, Ana; Sandoval Pickert, Fabio; Rezende, Danielle; Bandeira Lima, Julia; Oliveira Gil de Almeida, Yasmin; Lucindo Lakatos, Luiza; Carrara Folly Valente, Jaqueline; Augusto Rocha Pompermayer, Vinicius; Pereira Ramos Júnior, Sidney; Guimarães Cunha, Débora; Wagmacker Barbosa, Bárbara; et al. (Health and Society, 2025)
Morbid obesity is a chronic and progressive condition associated with various comorbidities, such as type 2 diabetes, hypertension and cardiovascular diseases. In the management of this condition, clinical treatments and surgical interventions have been widely debated, with metabolic surgery standing out as an alternative for cases refractory to clinical treatment. To compare the costs and efficacy of metabolic surgery and clinical treatment in the management of morbid obesity, assessing the economic impacts and clinical outcomes in the medium and long term. This is a literature review with a qualitative approach, based on studies available in the PubMed, Scopus and Web of Science databases. Health descriptors such as “Bariatric Surgery,” “Obesity Management,” and “Type 2 Diabetes Treatment” were used, covering the period from 2015 to 2023. The selection followed specific inclusion and exclusion criteria to ensure the relevance and quality of the articles included. Studies show that metabolic surgery is more effective in sustained weight loss and in controlling metabolic comorbidities, with type 2 diabetes remission rates of over 70%. In terms of costs, although the initial investment for the surgical procedure is high, there are savings in the long term due to the reduction in expenditure on medication, hospitalizations and monitoring of complications. In contrast, clinical treatment has lower initial costs, but often requires prolonged use of medication and interventions, with lower success rates in weight maintenance and remission of comorbidities. Metabolic surgery stands out as an effective and economically viable option for morbidly obese patients, especially those with severe comorbidities. However, the choice of treatment must be individualized, taking into account the surgical risks, the ability to adhere to lifestyle changes and the resources available in the health system.